1995
DOI: 10.1021/bi00006a003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Residues on CD40 and Its Ligand Which Are Critical for the Receptor-Ligand Interaction

Abstract: Interactions between gp39 (CD40L, TRAP, T-BAM) on activated T cells and CD40 on antigen-presenting cells play an important role in regulating antibody production by B cells, cytokine production by monocytes, and other immune responses which require T cell "help". Using structure-based sequence alignments, a molecular model of gp39, site-directed mutagenesis, and receptor-ligand binding assays, we have identified CD40 and gp39 surface residues which are important for receptor-ligand binding. Binding studies wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 31 publications
4
79
0
Order By: Relevance
“…Such structural restraint of the N terminus may also affect the way in which the ligand interacts with the receptor and explain the enhanced bioactivity. Site-directed mutagenesis has shown that Lys 143 and Tyr 145 are critical for CD40L interaction with CD40 (27). These residues are in close proximity to the N terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Such structural restraint of the N terminus may also affect the way in which the ligand interacts with the receptor and explain the enhanced bioactivity. Site-directed mutagenesis has shown that Lys 143 and Tyr 145 are critical for CD40L interaction with CD40 (27). These residues are in close proximity to the N terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Similar trees were obtained using maximum parsimony analyses and by systematically adding or removing sequences from the phylogenetic analyses. (22). A potential glycosylation site (Asn 240 ) described in human CD40L is indicated ( ‡) (22).…”
Section: Phylogenetic Analysis Of Teleost Tnfsf Membersmentioning
confidence: 99%
“…(22). A potential glycosylation site (Asn 240 ) described in human CD40L is indicated ( ‡) (22). Abbreviations: Hs, Homo sapiens; Mm, Mus musculus; Xt, X. tropicalis; Om, O. mykiss; Tn, T. nigroviridis.…”
Section: Phylogenetic Analysis Of Teleost Tnfsf Membersmentioning
confidence: 99%
See 1 more Smart Citation
“…With the TNF-␤/TNF receptor interaction in mind, Bajorath et al (29) have identified the CD40 and CD154 residues that are ؉ BJAB cells. BJAB (A) or U937 (B) cell lines were stimulated at 37°C with 250 ng of sCD154WT or each of its mutants for the indicated time points.…”
Section: Discussionmentioning
confidence: 99%